Self-Estimated functional inability because of pain questionnaire for workers: a reliability and construct validity study - Melo,Josane Soares Pinto (2021)
SUMMARY OBJECTIVE: The objective of this study was to investigate the reliability and construct validity of the Self-Estimated Functional Inability because of Pain questionnaire for workers in a sample of Brazilian workers with musculoskeletal pain. METHODS: This is a questionnaire validation study. Workers with musculoskeletal pain were included. Besides the Self-Estimated Functional Inability because of Pain questionnaire for workers, we used the following instruments to perform construct validity: the Work Ability Index and the Numerical Pain Rating Scale. A subsample answered the Self-Estimated Functional Inability because of Pain questionnaire for workers in two moments to calculate reliability by means of the intraclass correlation coefficient and internal consistency by means of the Cronbach’s alpha. RESULTS: A total of 190 Brazilian workers were included. Regarding the construct validity, we observed a correlation with magnitude above 0.50 between the Self-Estimated Functional Inability because of Pain questionnaire for workers and the Numerical Pain Rating Scale, given that these two instruments have similarity in the construct, and correlations above 0.30 between the Self-Estimated Functional Inability because of Pain questionnaire for workers and the domains 2, 3, and 4 of the Work Ability Index. Regarding reliability, we observed adequate reliability (intraclass correlation coefficient=0.864) and internal consistency (Cronbach’s alpha=0.807). CONCLUSION: The Self-Estimated Functional Inability because of Pain questionnaire for workers is a reliable and valid instrument to be used in Brazilian workers with musculoskeletal pain.